Literary and Graphic Visions of Death in 19th-century Illustrated Editions of the Polish Fictional Literature - Mirońska, Dąbrówka (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
The article is particularly concerned with the visions of death in 19th-century illustrated editions ofthe Polish fictional literature. The choice of conducting such research resulted from my interest in bookas an item which is produced as the effect of cooperation of many people: author, illustrator, editor andprinter. I treat the book as a whole, in which coexist both: the text and its graphic visualization.The investigation into the relations between iconic signs, on the one hand, and literary narration onthe other, emphasized the necessity of taking into account the relevant aspects of illustration as a specificway of communicating. The problems included, inter alia: how visual arts interpret the description ofliterary scenes and characters; in what way illustration explains, supplements as well as modifies thetext and intensifies its effects; why some literary scenes deserved to be graphically emphasized and theother ones did not; finally why the situation of illustration perversely “decoding” a message given by textoccurred. The “points of junction” of the literary and icon elements, the meaningful role of the latter, thereinterpretation of one work by another were also treated as the vital problems. The article consists of five parts which exemplify the main problem on selected examples. Thefirst part deals with general questions relating to the role of illustrations in 19th century. The secondpart is devoted specifically to the scene of death of main heroine in Maria, the 19th-century a poemby A. Malczewski, the most popular literary work among Polish artist at that time. The third part isconcerned with three examples of ars bene moriendi in Polish literature (H. Sienkiewicz Ogniem i mieczem,W. Pol Mohort and K. Suffczyński Zawsze oni). The last to be discussed in the fourth part are the scenesof cruel deaths (H. Sienkiewicz Pan Wołodyjowski, J. I. Kraszewski Stara baśń). The last part focuses onthe final conclusions.My research provided me with useful insights into the problem. The comparison between literarynarration with the way of the telling the same story by means of pictures unveiled the fact, that theillustrations established and codified ideological visions of the Polish history for many years. They werea critical instrument of building cultural code as well as national identity in the period of the partitionsof Poland. On the other hand, the conclusion deals with the problem of the text being “betrayed” bythe illustration as the visual representation modified the elements of the literary message. This situationoccurred very often in 19th century against common conviction of critics and researchers.